3D scintigraphic imaging and navigation in radioguided surgery: freehand SPECT technology and its clinical applications. (2nd April 2016) - Bluemel, Christina; Matthies, Philipp; Herrmann, Ken; Povoski, Stephen P.
ABSTRACT: Freehand SPECT (fhSPECT) is a technology platform for providing 3-dimensional (3D) navigation for radioguided surgical procedures, such as sentinel lymph node (SLN) biopsy (SLNB). In addition to the information provided by conventional handheld gamma detection probes, fhSPECT allows for direct visualization of the distribution of radioactivity in any given region of interest, allowing for improved navigation to radioactive target lesions and providing accurate lesion depth measurements. Herein, we will review the currently available clinical data on the use of fhSPECT: (i) for SLNB of various malignancies, including difficult-to-detect SLNs, and (ii) for radioguided localization of solid tumors. Moreover, the combination of fhSPECT with other technologies (e.g., small field-of-view gamma cameras, and diagnostic ultrasound) is discussed. These technical advances have the potential to greatly expand the clinical application of radioguided surgery in the future.